The Development of C9orf72-Related Amyotrophic Lateral Sclerosis and Frontotemporal Dementia Disorders - Qijie Yang; Bin Jiao; Bin Jiao; Lu Shen; Lu Shen (Frontiers in Genetics, 2020)
The expanded GGGGCC hexanucleotide repeat in the non-coding region of the C9orf72 gene is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). There are three main disease mechanisms: loss of function of C9ORF72 protein, gain of function from the accumulation of sense and antisense (GGGGCC)n in RNA, and from the production of toxic dipeptides repeat proteins (DPRs) by non-AUG initiated translation. While many of the downstream mechanisms have been identified, the specific pathogenic pathway is still unclear. In this article, we provide an overview on the currently available literature and propose several hypotheses: (1) The pathogenesis of C9orf72-associated ALS/FTD, which cannot be explained by a single mechanism, involves a dual mechanism of both loss and gain of function. (2) The loss of function and gain of function can cause TDP-43 aggregation and damage nucleocytoplasmic transport. (3) Neurodegeneration can be caused by an accumulation of toxic substances in neurons themselves. In addition, we suggest that microglia may cause neurodegeneration by releasing inflammatory factors to neurons. Finally, we summarize several of the most promising treatment strategies.